The Influence of Artificial Intelligence on the Strategic Communication Industry - Seriane Morapeli; Mammiki Khemisi (Communicare)
Artificial intelligence (AI) and the continuous advancements in technology have changed how individuals live and how organisations function. The move to automation questions the need for and value of manual labour, particularly in the field of strategic communication. It has raised concerns about the future of jobs in the communication field and the role of humans in these advancements. The principles of the theory of disruptive innovation are applicable to the study. This study aims to explore the role of AI in the strategic communication industry. Semi-structured interviews with communication professionals in the South African strategic communication industry were conducted to explore their knowledge of AI and its role in the industry. Participants indicated a basic knowledge of the role of AI in the industry, agreeing that AI offers the benefits of convenience and efficiency. However, human input should remain valuable and training in AI technologies should be prioritised. This study contributes to the limited research on the role of AI in the strategic communication industry in South Africa.